A study of an extension of the exponential distribution using logistic-x family of distributions - E.Oguntude, Pelumi; A.Khaleel, Mundher; O.Adejumo, Adebowale; I.Okagbe, Hilary (International Journal of Engineering and Technology, 2019)
Compound probability models have played important roles in modeling real life events; their ability to withstand skewed datasets has been attributed to the extra shape parameters they possess. This paper focused on exploring a two-parameter compound distribution; Logistic-X Exponential distribution. The basic mathematical properties of the model were obtained and established. The maximum likelihood method of estimation was adopted in estimating the model parameters. The application and potentials of the Logistic-X Exponential distribution were illustrated with the aid of two real data sets; its performance was also compared with the Logistic distribution and Exponential distribution. A simulation study was performed and the behavior of the model parameters was investigated.Â Â